2012
DOI: 10.1208/s12248-012-9342-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Lymph Node Uptake, and Mechanistic PK Model of Near-Infrared Dye-Labeled Bevacizumab After IV and SC Administration in Mice

Abstract: Abstract. Our objective was to determine the pharmacokinetics, bioavailability and lymph node uptake of the monoclonal antibody bevacizumab, labeled with the near-infrared (IR) dye 800CW, after intravenous (IV) and subcutaneous (SC) administration in mice. Fluorescence imaging and enzymelinked immunosorbent assay (ELISA) assays were developed and validated to measure the concentration of bevacizumab in plasma. The bevacizumab-IRDye conjugate remained predominantly intact in plasma and in lymph node homogenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
(32 reference statements)
1
26
0
Order By: Relevance
“…Comparable plasma concentration profiles for up to 24 hours measured by fluorescence and ELISA have been observed for bevacizumab with a high dye/protein labeling ratio (3.5) (Wu et al, 2012). Another study concluded that IRDye800 in a low dye/protein labeling ratio does not significantly alter the pharmacokinetics of cetuximab, which has a relatively short half-life at ASPET Journals on May 9, 2018 dmd.aspetjournals.org (2.5 days) (Zinn et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Comparable plasma concentration profiles for up to 24 hours measured by fluorescence and ELISA have been observed for bevacizumab with a high dye/protein labeling ratio (3.5) (Wu et al, 2012). Another study concluded that IRDye800 in a low dye/protein labeling ratio does not significantly alter the pharmacokinetics of cetuximab, which has a relatively short half-life at ASPET Journals on May 9, 2018 dmd.aspetjournals.org (2.5 days) (Zinn et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the V p was similar for control and pioglitazone-treated animals. Although a 2CM estimates V c and CL t similar to physiologically relevant volumes (28), there is the assumption that the clearance is only from the central compartment. Thus, V p values are limited in identifiability, and as such the significance of V p changes may not be physiologically relevant (29).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous chemotherapy targeted to regional lymph nodes increased lymph node drug concentration compared with intravenous delivery (165), although this method has yet to be tested in a spontaneous model of lymph node metastasis. Lipid nanoparticles also increased delivery of antiretroviral drugs to lymph nodes of primates (166).…”
Section: The Growth Of Lymph Node Metastasesmentioning
confidence: 99%